Multi – Function Umbrella / Siti Nor Athirah Mahmod - Mahmod, Siti Nor Athirah (2020)
Our product brand, Multi-purpose umbrella is actually a local product brand, specializing and participating in delivering a new approach of technology of the umbrella for the consumers. This product was established, to deliver a new products which adopts the principle of sustainability at which we try to offer an alternative of technology. This kind of umbrella will allow the consumers to continue living their lives, but with easier way when thay go outside. This product will focus on few types of target markets, gathered together as our possible customers. We are aiming to serve the customers in Malaysia, by least. Focusing primarily on demographic, psychographic and also geographic aspects, the target market is expected to form a vast group of 50, 000 customers within the first annum of business. Despite our fresh establishment and minor size compared to other dominator of industry like Xiaomi, we are able to thrive through the obstacles by owning few competitive advantages. The advantages includes provide with wind resistance technology, improvise with glow in the dark technology, automatically open and close button, water resistance, UV and IR resistance, provide with disposable plastic bag at the umbrella holder and durable and rustless.